Prawo do życia w traktatach międzynarodowych - Michalska, Anna (Wydział Prawa i Administracji UAM, 1984)
Provisions of the international treaties, both universal and regional, instituting the right to life are put by the authoress under examination and appreciation. Contents of the right to life is not univocally formulated in those treaties and in consequence a scope of its legal protection beco:mes a source of certain doubts. The treaties under discussion contain relatively numerous judicial guarantees persons sentenced to death penalty are entitled to, whereas an individual is protected against the arbitrary deprivation of life in an insufficient degree. A lack of precise definition of the notion „arbitrarily" is the reason for that as well as a lack (with the exception of the European Convention) of limits assigned in which organs of law and order can use physical force and put somebody to death in „non-arbitrary means". The treaties concerning 'human rights do not guarantee a conceived child the „right to be born". Decisions of international organs are sharing that opinion. Meanwhile other international acts (eg. declaration of rights of child, draft of the convention of rights of child) are inclining towards protection of conceived child. The studied treaties do not protect the right to life in face of such threats as: acts of terrorism, political homicides, emergency executions or practices of state organs resulting in „disappearances" of individuals. A new concept of the right to life appeared in the humanitarian law and in other international acts (eg. Declaration on Social Progress and Developement). They advocate not only a protection against arbitrary (deprivation of life but also set guarantees of a minimum standard of existence. All in all the „night to life" becomes to be understood as the „right to living", especially 'in the recently adopted international acts. That aspect has to be accounted for in discussions on the right to life in a wider scope than recently, as they have had too traditional limits set by problems of capital punishment and admissibility of abortion.
Right to life in the international treaties